Data-Driven Society Begins with Data-Savvy Youth. - Ercegovac, Zorana (Bulletin of the Association for Information Science & Technology)
EDITOR'S SUMMARY With data literacy an increasingly critical skill, dedicated instruction should start early in the educational process. By secondary school students should understand the distinction between data and information and the scope of the concept, and they should think critically about authorship, quality, source, collection, access, sharing and reuse. Instruction in data literacy requires access to large repositories of digital data, enabling students to develop skills in data description and tagging, prompting critical thinking about trustworthiness, reliability and validity, as well as audiences, temporal attributes, representations and evaluative sources. Data can be the focal point of a variety of classroom projects and integrated across disciplines, and there are many sources of data that can be readily accessed for classroom projects.